Answer:
Explanation:
Background: f(x) is the same thing as y but represents the value of x in parentheses.
Ej: f(2)=3x+2, this solution would be "8" because the value in the parentheses represents the value of x. (if the parentheses have an "x" then the value of x is unknown.
1.
f(x)=5x+8 g(x)=(x-8)/5
f(g(x))=?, 5((x-8)/5)+8
f(g(x))=x-8+8
f(g(x))=x
g(f(x))=5x+8-8/5
g(f(x))=5x/5
g(f(x))=x
g(f(x))=f(g(x)) because they both equal x proving they are inverses
Sorry, I don't have time to answer the rest of the steps (I will give the answers to check the work).
All of them are x=x because they are all inverse functions.